1997
DOI: 10.1111/j.1540-8159.1997.tb03563.x
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Therapy of Cardioinhibitory Syncope in Pediatric Patients

Abstract: A small percentage of pediatric patients with neurally mediated syncope will have an asystolic response during upright tilt table testing. The purpose of this study is to evaluate the incidence of asystole during tilt table testing, and to assess the outcome of medical management of such patients. Of 398 patients undergoing evaluation for recurrent syncope between January 1989 and 1994, 18 (4.5%) experienced asystole lasting > or = 5 seconds during baseline tilt test. Patients had experienced a mean of four ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…Our data indicate a relationship between recurrences and the number of previous syncopes but not the chosen therapy. Thus, in agreement with other authors [3,13,18,21,27,28] and considering our large cohort of patients (with a mean time free of recurrence of 92·6 months and without any cardiac death), we do not believe that pacemakers should be considered routinely as first choice therapy. This is substantiated by the fact that we and other authors (e.g.…”
Section: Long-term Outcome Of Patients With Asystole Induced By Head-supporting
confidence: 91%
See 2 more Smart Citations
“…Our data indicate a relationship between recurrences and the number of previous syncopes but not the chosen therapy. Thus, in agreement with other authors [3,13,18,21,27,28] and considering our large cohort of patients (with a mean time free of recurrence of 92·6 months and without any cardiac death), we do not believe that pacemakers should be considered routinely as first choice therapy. This is substantiated by the fact that we and other authors (e.g.…”
Section: Long-term Outcome Of Patients With Asystole Induced By Head-supporting
confidence: 91%
“…Furthermore, Grubb et al [19] described an asystolic response (>4000 ms) in 10 (20%) of 50 patients with recurrent syncope, whereas Brignole et al [20] reported on 28 patients (18%) with asystole (d3000 ms) among 152 consecutive patients. Deal et al [21] described a lower (4·5%) incidence of asystole (d5000 ms) among 398 consecutive paediatric patients. In Spain, Pérez-Paredes et al [22] published their experience with a cohort of 12 patients with asystole.…”
Section: Prevalence and Duration Of Asystolementioning
confidence: 98%
See 1 more Smart Citation
“…In uncontrolled studies, betablockers [399,402,404] , alpha-fludrocortisone [399,402] and alpha-agonists [405] have been supposed be efficacious in the paediatric age group (level B). Even in the instance of cardioinhibitory syncope with an exaggerated asystolic response, a pacemaker should be avoided whenever possible; as an alternative, effective management with pharmacological therapy without the need for pacemaker implantation has been shown [406] . Breath-holding spells generally do not require specific therapy unless connected with longer asystole associated with potential cerebral injury [22,392] .…”
Section: Therapymentioning
confidence: 99%
“…The incidence was higher during nitrate provocation test (21%) than during passive head-up tilt test (14%) [4]. Up to now only two papers specifically examined the outcome of tilt-induced asystole in adult patients [5] and pediatric population [6] and the exact clinical and prognostic significance of this condition is still a matter of debate [7].…”
Section: Introductionmentioning
confidence: 99%